France : Selected Issues. (IMF Staff Country Reports; Country Report, 2004)
This Selected Issues paper on France underlies public intervention in financial markets. Econometric analysis indicates that in the long term, consumption tracks disposable income closely but is also affected by wealth effects. A counterfactual exercise suggests that a lower return to experience could be responsible for lower early wage growth in France. Increased training could enhance the employment experience of the low-skilled young worker in France provided that its cost is shared between the employer and the employee.